A critical inquiry into the evolution of socio-political performances in traditional Nigeria Yoruba Alarinjo and contemporary itinerant theatre through a review of selected works of Hubert Ogunde, Wole Soyinka, Ola Rotimi and Femi Osofisan - Bakare, Babatunde Allen (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.